On Existence of Fixed Points for Multivalued Contractive Type Mappings in Quasi-Metric Spaces (Contemporary Mathematics, 2024)
We present fixed point results for multivalued contractive type mappings via Q-function on quasi-metric spaces. Our main results supported with example. Consequently, our results either improve or generalize several known results of metric fixed point theory.
Keywords: quasi-metric space; fixed points; multivalued mappings; Q-function; Ω[0, F]